2018
DOI: 10.1111/imm.13013
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of antimicrobial and phagocytic programs in human macrophages

Abstract: Summary Macrophage (MΦ) polarization is triggered during the innate immune response to defend against microbial pathogens, but can also contribute to disease pathogenesis. In a previous study, we found that interleukin‐15 (IL‐15) ‐derived classically activated macrophages (M1 MΦ) have enhanced antimicrobial activity, whereas IL‐10‐derived alternatively activated macrophages (M2 MΦ) were highly phagocytic but lacked antimicrobial activity. Given that the ability to modulate MΦ polarization from M2 MΦ to M1 MΦ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Indeed, it seems to be possible to re-educate macrophages from a classical so-called M1 to M2 phenotype and vice versa. (113) New technologies (sequencing techniques, imaging methods, unbiased big data analyses) allow for an exciting and fresh view on macrophage heterogeneity, for instance, regarding origin, polarization, localization in tissue, and function in relation to the disease state. (114) However, it is important to accurately describe the experimental setting from which conclusions are drawn to allow comparability between models and researchers.…”
Section: Spectra and Fluidity Of Macrophage Polarization Statesmentioning
confidence: 99%
“…Indeed, it seems to be possible to re-educate macrophages from a classical so-called M1 to M2 phenotype and vice versa. (113) New technologies (sequencing techniques, imaging methods, unbiased big data analyses) allow for an exciting and fresh view on macrophage heterogeneity, for instance, regarding origin, polarization, localization in tissue, and function in relation to the disease state. (114) However, it is important to accurately describe the experimental setting from which conclusions are drawn to allow comparability between models and researchers.…”
Section: Spectra and Fluidity Of Macrophage Polarization Statesmentioning
confidence: 99%
“…Macrophages are plastic populations and can display various functions simultaneously or in sequence. The possibility to reprogram or repolarize macrophages into different phenotypes and functions [36] holds great potential for targeting these cells for the treatment of liver diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…In an anti-inflammatory profile (M2), this cell induces increased uptake of lipids [21,22] and Hb-haptoglobin [16,42], which aid the growth of M. leprae by the activation of the enzymes IDO [42,45], HO-1 [42] and arginase [37]. On the other hand, in a pro-inflammatory and microbicidal profile (M1), the macrophage produces TNF [26,48], IL-6 [37,48,49], and IL-15 [22,37,39] besides being able to stimulate T cells to produce IFN-γ [34]. In addition, these M1 macrophages induce autophagy [57,58], an important process of homeostatic regulation recently described with the immunological role [56], which acts on infection control.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of paucibacillary tuberculoid and reversal reaction (an acute inflammatory clinical condition associated with increased levels of IFN-γ in leprosy patients) patients' skin lesions demonstrated that macrophage subtypes with microbicidal and homeostatic functions are spatially distributed in tuberculoid granulomas according to the specific microenvironments [38]. The center of the tuberculoid granulomas appears to be populated by pro-inflammatory CD68 + CD163 − M1 macrophages, responsible for containing the infection, while the periphery is composed of anti-inflammatory CD68 + CD163 + M2 macrophages, tasked with limiting tissue damage caused by the M1 macrophage antimicrobial activity [39]. Accordingly, Montoya and colleagues [22] proposed two different macrophage functional programs for the polar clinical forms of leprosy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation